Effect of varieties and planting dates on yield-attributing characters in onion (Allium cepa) (Current Horticulture, 2024)
The experiment was conducted at farmers’ fields during the 2020-21 season to evaluate the effects of varieties and planting dates  on onion yield parameters. The highest bulb yield was recorded in T3, followed by T4, T2, and T1. Similarly, D2 exhibited the  highest yield, followed by D3 and D1. T4 also resulted in the maximum plant height, average bulb weight, and bulb diameter.  The planting date significantly influenced bulb weight and plant height. Consequently, T3 (PRO-6) demonstrated the highest  benefit-to-cost ratio and yield, followed by T4 (PRO-7), T2 (Punjab Naroya), and T1 (farmers’ practices). Among the planting  dates, D2 yielded the highest, with a benefit-to-cost ratio of 4.58, followed by D1 (4.42) and D3 (4.35). The combined effects  indicate that PRO-6, along with a planting date of January 1st, resulted in the maximum yield and profit.
Keywords: Variety; Planting date; Bulb yield; Economics